AN INVESTIGATION INTO BARRIERS LIMITING ACCESS TO QUALITY BASIC EDUCATION AMONG POOR AND UNDERPRIVILEGED CHILDREN IN THE OUTSKIRT OF JIMETA, ADAMAWA STATE OF NIGERIA - Mohammed, Aisha Kadiri; Yahaya , Abdulrasheed; Ibrahim , Umar Jongur; Salawu, Basira Bisi; Umar , Fatima A; Esther Daniel , Mshelbila (Top Educational Review Journal (TERJ), 2024)
This study explores the barriers to accessing basic education among the poor, economically exploited and underprivileged children in Jimeta Outskirt, Yola North LGA of Adamawa State. The primary objectives of this study are to identify the factors limiting access to education, the availability and effectiveness of government policies that are aimed at addressing these barriers. The findings reveal that socioeconomic factors, including widespread poverty, cultural beliefs, and inadequate infrastructure, significantly hinder children’s ability to attend school. Furthermore, the study highlights the gap between the intent of government initiatives, such as the Universal Basic Education (UBE) Act, and their actual implementation, particularly in underserved communities. Challenges such as insufficient funding, lack of educational resources, and neglect of remote areas reduce the effectiveness of these policies. The findings underscore the need for comprehensive community-based interventions, improved policy execution, and enhanced resource allocation to bridge the educational gap. Addressing these barriers is critical for ensuring that all children, regardless of their socioeconomic background, have access to quality basic education.